Integration of inverter constraints in geometrical quantification of the optimal solution to an MPC controller - Raath, J.; du Toit Mouton, H.; Geyer, T. (IEEE Xplore: Control and Modeling for Power Electronics (COMPEL), 2016 IEEE 17th Workshop, 2017)
This paper considers a model predictive controller with reference tracking that manipulates the integer switch positions of a power converter. It can be shown that the optimal switch position can be computed without solving an optimization problem. Specifically, in a new coordinate system, the optimization problem can be solved offline, leading to a polyhedral partition of the solution space. The optimal switch position can then be found using a binary search tree. This concept is exemplified for a three-level single-phase converter with an RL load.
Published Conference Proceedings
Keywords: Model Predictive Control; Vector Quantization; Delaunay triangulation; Voronoi diagram; Binary Search Tree